On the ongoing computation of the LVR-15 reactor fuel burnup - Jan Pinta (Acta Polytechnica CTU Proceedings, 2022)
Isotopic composition of the LVR-15 reactor fuel changes significantly during the operation time. In order to enable Monte Carlo calculations of the LVR-15 core throughout any reasonable time period, the isotopic compositions of partially depleted fuel assemblies have to be known at the start of the simulation. Even though the infinite lattice calculation can represent useful initial approximation, the non-leakage assumption is not necessarily valid for compact and highly heterogenous cores like in case of the LVR-15. Therefore, a more advanced calculation process have to be implemented towards appropriate determination of fuel assembly burnup. The main aim of this paper is to describe the current state of the ongoing computation as well as provide an explanation of the chosen calculation scheme of the LVR-15 operation history. Currently available results that are affected by profound inaccuracy are discussed in the final part alongside with planned future improvements.